2018
DOI: 10.25134/erjee.v6i2.1256
|View full text |Cite
|
Sign up to set email alerts
|

Students� and Lecturers� Perception on Academic Writing Instruction

Abstract: The aim of this research is to gain the perception of students and lecturers toward academic writing instruction Indonesian language classes in Universitas Sriwijaya. This current research was a part of research and development study on Moodle-based teaching model for academic writing instruction in Indonesian language classes. The steps of research and development model was carried out using survey and content analysis. The research was conducted in Universitas Sriwijaya. Questionnaire, interview and focus-gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 5 publications
0
7
0
1
Order By: Relevance
“…Concerning to study in higher education, students are necessary to attain academic writing ability since it influences their academic achievement (Oktarina, Emzir, & Rafli, 2018). Students in university level should master the way to write well.…”
Section: Introductionmentioning
confidence: 99%
“…Concerning to study in higher education, students are necessary to attain academic writing ability since it influences their academic achievement (Oktarina, Emzir, & Rafli, 2018). Students in university level should master the way to write well.…”
Section: Introductionmentioning
confidence: 99%
“…Every student must have the ability to write. Writing ability or academic writing ability is needed by students to achieve academic achievement (Oktarina et al, 2018). Students at the university or college level must be able to write well.…”
Section: Introductionmentioning
confidence: 99%
“…Many factors influenced by this condition, the internal factor, as a study held by Kurniasih (2013) found that the linguistics aspect became a difficulty for the learners to write well. It probably comes from the external factor such as the learners' lack of learning motivation (Oktarina et al 2018), the materials did not follow the learners' needs (Sumarsono et al 2017), and the learners used general textbooks.…”
Section: Introductionmentioning
confidence: 99%